PEMBERIAN SANKSI BERUPA PEMBEBASAN JABATAN OLEH BUPATI DI KOTAWARINGIN TIMUR KALIMANTAN TENGAH - Ernawati; Pamungkas, Yogo; Ernawati, Ernawati (Reformasi Hukum Trisakti, 2023)
Sanggul is a State Civil Apparatus who has brought the "Decree of the East Kotawaringin Regent Concerning Disciplinary Punishment for Exemption from Position" to the Palangkaraya State Administrative Court as the subject of the dispute. The issue with this article is that the steps used by the Kotawaringin Timur regent to inspect Sanggul and impose sanctions on his dismissal from office in Decision 3/G/2021/PTUN.Plk were not in accordance with the steps outlined in PP No. 53/2010 on Civil Service Discipline. The research methodology employed is normative juridical, which analyzes primary and secondary evidence before drawing inferences based on qualitative analysis. The findings of this study show that the Kotawaringin Timur regent's methods for applying disciplinary sanctions were procedurally faulty since they did not follow the PP above. According to the study's findings, because the Kotawaringin regent did not follow the inspection procedure exactly as required by the government regulation on civil servant discipline, he was deemed careless and negligent in carrying out the administrative stages. The East Kotawaringin regent then brought about the repercussions of not achieving the requirements of Articles 23 and 24 of the PP above.